Sharing landscapes with megaherbivores: Human-elephant interactions northeast of Tarangire National Park - Justin Raycraft; George Tanner; Edwin Maingo Ole (Environmental Challenges)
The rising elephant population in Tarangire National Park of northern Tanzania has led to increasing human-elephant interactions in dispersal areas to the northeast of the park. While the movement dynamics of elephants across the landscape are well documented, anthropological dimensions of human-elephant coexistence warrant more research. The present study used stratified random sampling to survey 1076 people living across twelve villages surrounding Manyara Ranch and Randilen Wildlife Management Area (WMA) about their lived experiences, perceptions, attitudes, and tolerance towards elephants. Villages between Manyara Ranch and Randilen WMA reported regular conflicts with elephants, while those to the west of the ranch did not consider elephants to be a major concern. Crop raiding was particularly frequent in Makuyuni, Lengoolwa, Mswakini Juu, Mswakini, Lemooti, and Nafco. Economic impacts of elephant crop raiding ranged from as low as $4USD per household per year in Lolkisale to approximately $812 per year in Mswakini, and accounts of property damage were most severe in Makuyuni and Naitolia. The vast majority of respondents (96 %) did not have a household member who had been injured by elephants over the preceding twelve-month period, suggesting that elephant attacks on humans were relatively infrequent on the whole. However, between 10 and 24 % of participants in Lemooti, Nafco, Mswakini, and Mswakini Juu noted injuries incurred in the past year. Different ethnic groups had statistically significant differences in their attitudes towards elephants. People with higher levels of education had more positive attitudes towards elephants, and elders had more negative attitudes than youth. Elephants disturbed the sleep of men more than women highlighting the gendered dimensions of human-wildlife interactions. Despite these visible and hidden costs of elephants, most people (72 %) across the whole study area were somewhat tolerant of elephants, except in Makuyuni, Lengoolwa, and Nafco where seasonal crop raiding was severe and tolerance for elephants was extremely low. People in those villages, as well as Mswakini Juu and Mswakini, were largely in favor of government-sanctioned culling, though 94 % of all respondents viewed elephant poaching as bad. Tolerance towards elephants was negatively correlated with livestock holdings and positively associated with total farm size. Greater attention to community perspectives is necessary for promoting human-elephant coexistence in the Tarangire ecosystem.